Tailored Design of Mesoporous Nanospheres with High Entropic Alloy Sites for Efficient Redox Electrocatalysis - Nandan, Ravi; Nara, Hiroki; Nam, Ho Ngoc; Phung, Quan Manh; Ngo, Quynh Phuong; Na, Jongbeom; Henzie, Joel; Yamauchi, Yusuke (Wiley-VCH Verlag, 2024)
High Entropy Alloys (HEAs) are a versatile material with unique properties, tailored for various applications. They enable pH-sensitive electrocatalytic transformations like hydrogen evolution reaction (HER) and hydrogen oxidation reactions (HOR) in alkaline media. Mesoporous nanostructures with high surface area are preferred for these electrochemical reactions, but designing mesoporous HEA sis challenging. To overcome this challenge, a low-temperature triblock copolymer-assisted wet-chemical approach is developed to produce mesoporous HEA nanospheres composed of PtPdRuMoNi systems with sufficient entropic mixing. Owing to active sites with inherent entropic effect, mesoporous features, and increased accessibility, optimized HEA nanospheres promote strong HER/HOR performance in alkaline medium. At 30 mV nominal overpotential, it exhibits a mass activity of approximate to 167 (HER) and 151 A gPt-1 (HOR), far exceeding commercial Pt-C electrocatalysts (34 and 48 A gPt-1) and many recently reported various alloys. The Mott-Schottky analysis reveals HEA nanospheres inherit high charge carrier density, positive flat band potential, and smaller charge transfer barrier, resulting in better activity and faster kinetics. This micelle-assisted synthetic enable the exploration of the compositional and configurational spaces of HEAs at relatively low temperature, while simultaneously facilitating the introduction of mesoporous nanostructures for a wide range of catalytic applications. A micelle-assisted wet-chemical method is used to design and synthesize mesoporous high-entropy alloy nanospheres at low temperatures. By adjusting reaction conditions, the structure and morphology of these nanospheres can be tailored, resulting in a crystalline state akin to that of a single element. The optimized nanospheres offer new insights into electrochemical catalytic reactions, exhibiting remarkably fast kinetics. image